Peningkatan Hasil Belajar Siswa Melalui Metode Everyone Is A Teacher Here Mata Pelajaran Akidah Akhlak Siswa Kelas III MI Ta’limus Shibyan Rejoso Pasuruan - Nasikha, Abdin; Hidayah, Noer; Yusuf, Moh. Asror (Allimna: Jurnal Pendidikan Profesi Guru, 2022)
The problem to be answered in this research is whether the Everyone Is A Teacher Here method can improve attention, motivation, and learning outcomes of students in the moral aqidah subjects about commendable morals in third grade students of MI Ta'limus Shibyan in the 2021 / 2022 academic year. In accordance with The type of research chosen is classroom action research, so this research uses a spiral-shaped research model from one cycle to the next. Each cycle includes action planning, application of action, observation and evaluation of the process and results of action, reflection. The step in the next cycle is carrying out the revised planning, action, observation and reflection. Before entering the first cycle, preliminary actions were carried out in the form of problem identification. The research instruments used in this study consisted of: syllabus, lesson plans, observation sheets, instrument sheets, and formative tests. To analyze the success rate or percentage of student success after the teaching and learning process at the end of each round, an evaluation in the form of a written test is carried out. This analysis is calculated using a simple technique, namely: (1) Assessing the results of formative tests/tests, (2) Assessing learning completeness. The results showed that student learning outcomes using Everyone Is A Teacher Here increased. This increase can be seen through every cycle that has been carried out